Are leftist or rightist voters better substantively represented? The effects of variance in district magnitude on party-voter ideological congruence. (April 2023) - Best, Robin E.
Abstract: How does the variation in district magnitude in districted proportional representation systems affect congruence between a voter and their party of choice? I argue that voters in large-magnitude districts will have higher levels of party-voter congruence than voters in small-magnitude districts, due to stronger strategic incentives and reduced party options in small-magnitude districts. Furthermore, I argue that this relationship will be stronger among leftist voters compared to rightist voters, due to the concentration of rightist voters in rural, small-magnitude districts and leftist voters in urban, high-magnitude districts. These expectations are tested using data that from 45 elections in 12 districted proportional representation systems included in the Comparative Study of Electoral Systems (CSES). The results support the expectation that party-voter ideological congruence will be higher for voters in larger electoral districts, and lower for voters located within smaller districts. Leftist voters do appear to suffer a congruence penalty in smaller districts, whereas the congruence of rightist voters is less affected by district magnitude. An examination of the mechanisms behind this finding suggests that leftist-voters in small-magnitude districts are faced with a smaller and more right-leaning set of party options.